Suicide Attempts Using Medications During the COVID-19 Pandemic in the State of Piauí - Francisco Patricio de Andrade Júnior; Jonathan Cordeiro de Morais; Rayanne Santos Alves; Gilberlânio Campos de Oliveira; Manoel Almeida Gonçalves Júnior; José Iury Ferreira Pires; Gabriel Ribeiro Costa; Kariny Gardênya Barbosa Lisbôa de Mélo; Franklin de Souza Sabino; Francisco de Assis Medeiros Maia; Rafael Gomes Firmino (REVISTA CEREUS, 2025)
Attempts of suicide represent a significant public health issue, exacerbated during the COVID-19 pandemic due to social isolation and the increase in mental disorders. This study aimed to analyze the epidemiological profile of suicide attempts involving medications in Piauí between 2020 and 2022. It is an epidemiological, retrospective study based on SINAN data. Variables such as year, gender, age group, ethnicity, and education level were analyzed, with calculations of simple and relative frequencies and the use of the Chi-Square test (p<0.05). Between 2020 and 2022, 2,155 suicide attempts were recorded, with the highest number occurring in 2022 (38.2%). Most cases involved women (80.6%), particularly those aged 20 to 39 years (47.8%), of mixed ethnicity (52%), and with a high school education (18.6%). The lethality rate was 0.23%, and complete recovery without sequelae was the main clinical outcome (69.2%). The increase in cases over time may be attributed to the exacerbation of pandemic effects, such as social isolation and financial stress. Thus, public policies focused on mental health, access to psychological support, and medication control are essential to address this challenge and reduce the rates of morbidity and mortality associated with it.